A cross sectional study on internet addiction among students of KMCT integrated campus - Mohandas, Bindu; T Pawar, Anant; John, Annie; Kumar K., Durgesh; P.K., Sujesh (Public Health Review: International Journal of Public Health Research, 2019)
Background: College students are vulnerable for developing dependence on the Internet, more than most other segments of the society. Studies on pathological internet use in India especially Kerala are scanty. So this study was conducted to find out internet addiction among college students. Objectives: 1) To find out the prevalence of internet addiction among the college students 2) To study the pattern of internet usage among these students. Methods: This cross-sectional study was carried out in students of four different colleges under KMCT Group of Institutions in Kozhikode, Kerala 2016-17. The data was collected by self- administering questionnaire consisting of socio demographic information, internet usage and Young’s Internet Addiction Test (YIAT). Data collected was entered in Microsoft excel and analyzed using SPSS. Prevalence of internet addiction was determined based on total score of YIAT. Result: The mean age of the study participants was 20.25±1.3SD. About 48.3% were males and 51.7% females. The mean age of computer use and internet use was 10.01 ± 3.55 years and 6.61 ± 3.13 years respectively. Prevalence of internet addiction was 77.6% in mild users and 18.4% in moderate users. 49.24% accessed internet during night time. 94.86% had internet connection in their smart phones and it was the most common device used for accessing internet. 93.1% said that internet helps in improving their academics. 43.5% visited various sites for more than ten times a month for academic purposes. 14.5% visited various sites on internet when they get time in between lecture classes and 7.1% visited different sites during an ongoing lecture. Conclusion: The results highlight the vulnerability of professional college students to internet addiction.